The polyol process: a unique method for easy access to metal nanoparticles with tailored sizes, shapes and compositions. (14th June 2018) - Fiévet, F.; Ammar-Merah, S.; Brayner, R.; Chau, F.; Giraud, M.; Mammeri, F.; Peron, J.; Piquemal, J.-Y.; Sicard, L.; Viau, G.
Abstract : This review aims to give a comprehensive account of the strategies used to prepare mono metallic nanoparticles and multimetallic materials in liquid polyols and to exemplify the potential of this method. Abstract : After about three decades of development, the polyol process is now widely recognized and practised as a unique soft chemical method for the preparation of a large variety of nanoparticles which can be used in important technological fields. It offers many advantages: low cost, ease of use and, very importantly, already proven scalability for industrial applications. Among the different classes of inorganic nanoparticles which can be prepared in liquid polyols, metals were the first reported. This review aims to give a comprehensive account of the strategies used to prepare monometallic nanoparticles and multimetallic materials with tailored size and shape. As regards monometallic materials, while the preparation of noble as well as ferromagnetic metals is now clearly established, the scope of the polyol process has been extended to the preparation of more electropositive metals, such as post-transition metals and semi-metals. The potential of this method is also clearly displayed for the preparation of alloys, intermetallics and core–shell nanostructures with a very large diversity of compositions and architectures.